Utilization of Nanotechnology for the Management of Plant-parasitic Nematodes - Gitanjali Devi (Archives of Current Research International, 2024)
Plant-parasitic nematodes are the major problem in food production. Management methods are based on mainly synthetic chemicals. Chemical nematicides are undesirable due to health and environment issues. Therefore, other novel technologies or materials are needed to be evolved for the management of plant-parasitic nematodes. Nanotechnology is one of the potential and innovative technologies for the management of various phytopathogens. Many nanoparticles have a useful nematicidal effect. This review presents the mode of action of different nanoparticles which are being used for the management of plant-parasitic nematodes.